Upaya Penguatan Literasi Anak Usia Dini melalui GERDASI - Desty Putri Hanifah; Rochyani Lestiyanawati (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2023)
This activity aimed to strengthen the literacy movement in early childhood through the habit of reading aloud at school and home. Gerdasi was a series of literacy-strengthening programs implemented at Kindergarten/RA Al Hidayah in the form of reading aloud at school and socializing the selection of children's books for parents. Gerdasi was held in April-June 2023 and attended by all children and parents/guardians of Kindergarten/RA Al Hidayah. The stages of implementing the community service activities included: 1) laying the foundation; 2) research design; 3) data gathering and analysis; and 4) acting on findings. Based on observations during reading-aloud activities, the data showed that more than 90% of children liked reading-aloud activities and enjoyed every discussion process. However, children's interest in books is not facilitated well at home. These findings became the basis for carrying out follow-up efforts in the form of socializing the selection of children's books with parents/guardians as the target. This socialization explained important points about literacy facts, choosing good children's books, as well as alternatives for choosing e-books. It was hoped that parents' knowledge regarding sites that provide e-books for children's storybooks could be an inspiration for parents to provide children with affordable reading materials